2020
DOI: 10.1128/jmbe.v21i1.1947
|View full text |Cite
|
Sign up to set email alerts
|

An Undergraduate Elective Course That Introduces Topics of Diversity, Equity, and Inclusion into Discussions of Science

Abstract: In this Science, Ethics, and Society elective undergraduate course at the St. Louis College of Pharmacy, students consider topics that scientists face continuously, including human and animal subjects, science denial, treatment of scientists, who owns and funds science, personalized medicine and genetics, health disparities, and scientific integrity, all through lenses of inclusion and equity. Students read primary and secondary literature pertaining to each day’s topic, upload reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Whether it has been through collegiate classes or departmental seminars, data has shown that conversational series such as our DEI discussions have paramount effects in improving diversity and inclusion. This discussion-based format has been seen to increase the understanding of the minority experience in STEM 8 , significantly increase self-perception and implicit bias 9 , and has been shown to increase feelings of inclusion within underrepresented minority groups 10 . In addition to social changes, DEI discussions have also created tangible change, such as increasing faculty hiring of underrepresented minorities and, overall, creating a more diverse workforce 11 .…”
Section: Rationalementioning
confidence: 99%
“…Whether it has been through collegiate classes or departmental seminars, data has shown that conversational series such as our DEI discussions have paramount effects in improving diversity and inclusion. This discussion-based format has been seen to increase the understanding of the minority experience in STEM 8 , significantly increase self-perception and implicit bias 9 , and has been shown to increase feelings of inclusion within underrepresented minority groups 10 . In addition to social changes, DEI discussions have also created tangible change, such as increasing faculty hiring of underrepresented minorities and, overall, creating a more diverse workforce 11 .…”
Section: Rationalementioning
confidence: 99%
“…Other institutions have worked to enhance underrepresented students' academic skills and the supports provided to these students, such as group study sessions focused on complex problems (e.g., Treisman, 1992) and expanded opportunities for training, mentorship, and cohort-building (see the Meyerhoff Scholars Program at the University of Maryland, Baltimore County; Hrabowski, 2019). Finally, faculty at other institutions have developed courses aimed at raising students' awareness of the challenges and ethical issues related to diversity, equity, and inclusion in the natural sciences as a component of their undergraduate science curriculum (e.g., Hudgings & Dalton, 2019;Reese, 2020). While many of these approaches provide documented improvements in underrepresented students' retention in STEM, in this paper we discuss our alternative approach-one which arose from a moment of campus conflict and reckoning, that has been developed through intensive partnership with students, and results in student-led action projects to increase all students' abilities to thrive in STEM.…”
Section: Other Institutional Efforts Towards Inclusive Stem Educationmentioning
confidence: 99%
“…Given the way in which ethics and science are interwoven in medical practice, we asked the question whether ethics could be integrated in biomedical science curriculum of pre-clinical medical training. While a review of literature has revealed recent efforts to implement ethics education into science education [23][24][25][26], we couldn't find any discussion of efforts to embed ethics curriculum within the biomedical science curriculum in particular, except for anatomy [27].…”
Section: Introductionmentioning
confidence: 98%